In the Nation We Trust: National Identity as a Substitute for Religion - Kenneth Harttgen; Matthias Opfinger (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2012)
We construct an index for national identity using information from the World Values Survey on peoples attitudes concerning politics and to the state itself. We then analyze the relationship between our new measure of national identity and social heterogeneity. The results indicate that religious diversity is significantly and positively related to national identity, whereas other variables proxying social heterogeneity are not. We argue that national identity is a substitute for religion. At high levels of religious diversity people do not identify with their religious group. They search other objects of identification offering common values and norms. Hence, people identify at the national level. Furthermore, democratic institutions and mobility throughout the country affect national identity positively.
Keywords: J15; O1; Z12; 330; National Identity; Social Heterogeneity; Religious Diversity; Common Beliefs